Características familiares y su relación con factores asociados en adultos mayores con fractura de cadera en la ciudad de Loja, 2016. - Burneo Yaguana, Omaira Ximena (2017)
Senior citizens are a fundamental part of our society. With the passage of time, there has been an increase in life expectancy for this population worldwide. Among the main pathologies presented by this population is hip fracture, which is considered to be of high morbidity and mortality and is also associated with social, economic and psychological factors that may affect family function. A quantitative, non-experimental, cross-sectional study of correlation was carried out in the province of Loja during 2016. The study sample comprised elderly adults with hip fracture. In order to assess the interrelationship between family factors and clinical characteristics, socio-demographic and unmet basic needs, 45 patients admitted to provincial hospitals and San Augustin Hospital Clinic in the city of Loja were chosen to be the study sample via the application of convenience sampling. An Unmet Basic Needs Questionnaire (NBI) pertaining to the Ecuadorian National Statistics and Census Institute (INEC), an evaluation of performance in activities of daily living (Barthel Index) and the Family Functionality Survey (APGAR) were all used. It was concluded that there is no relation between family characteristics with the clinical, socio-demographic and socioeconomic factors; except between the occupation of the elderly and gender. Keywords: family, loneliness, aging, couple, life cycle.